PAPR reduction method for SFBC MIMO-OFDM systems - SHA Yi; CHEN Jun-xin; WANG Guang-xing (Tongxin xuebao)
The high PAPR is the major drawback of SFBC MIMO-OFDM systems to its practicability. To deal with this problem, a novel method was proposed to reduce the PAPR of SFBC MIMO-OFDM systems. It was called PIP（polyphase inversion and permutation） method. The method treated all transmit antennas as a whole. By dividing, rotating, and shifting the sequence twice, the method fully made use of the character of conjugation and shifting of all the antennas’ sub-carriers. Meanwhile, PIP method could reduce the complexity of calculation by using the character of IFFT. The simulation result proves the method to be efficient.